Professional Maritime Education Impact on Supply Chain Economic Optimization in Global Trade - Barasa, Larsen; Cahyadi, Tri; Simanjuntak, Marihot (Meteor STIP Marunda, 2025)
This research examines how comprehensive maritime education prepares professionals for supply chain economic management and global trade impact assessment. Through qualitative analysis of ten Nautical Deck Engineering graduates with ten-year vocational maritime education and current leadership positions in shipping industries, the study investigates educational preparation effectiveness for economic competency development. The research employs phenomenological analysis, thematic examination, and narrative synthesis to understand professional competency evolution from educational foundation through career advancement. Results demonstrate exceptional performance across measured competency dimensions, with Supply Chain Economic Performance Index scores of 4.7 and Global Trade Economic Integration Coefficient scores of 4.6 out of 5.0. Participants generated $69.5 million annual economic value through supply chain optimization, cost reduction, and strategic positioning improvements. Thematic analysis reveals four primary competency development categories: educational foundation excellence, professional competency evolution, supply chain economic optimization, and global trade impact understanding. The findings indicate that comprehensive maritime education effectively develops analytical capabilities, strategic thinking competencies, and economic understanding essential for professional excellence in supply chain management contexts, providing substantial return on investment in maritime education and professional development.